PENERAPAN TEKNIK KONSELING EKLEKTIF DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA - Nurlis, Nurlis (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This study aims to determine the improvement of student learning outcomes by applying guidance and counseling Attending elective techniques. This type of research is classroom action research. The subjects of this study were students of class VII-7 SMP N 1 Simpang Empat who had the same problem totaling 3 students. The results of the analysis of the personality development of students in the first cycle obtained a value of 47.50 with a less good category. The results of the analysis of the personality development of students in the second cycle obtained a value of 74.17 with a fairly good category, with an increase of 26.67 and an average score of 6.83. Besides the activities of the teacher fostering students with Attending Eklective techniques in the first cycle is quite good, namely 61.67. While the activities of the teacher fostering students with Attending Elective techniques in cycle II scored 90 with very good categories. Based on data from the interviews of students who were guided using the technique of Attending Attendance in the first cycle and second cycle was quite active in following the teaching and learning process. From the results of data analysis in the first and second cycles, it can be seen that there is an increase in students' ability to solve problems faced and student learning achievement in class using Attending Elective Techniques. Keywords: counseling, eclectic attending Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa dengan menerapkan bimbingan dan konseling teknik eklektif Attending. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian ini adalah siswa kelas VII-7 SMP N 1 Simpang Empat yang memiliki permasalahan sama berjumlah 3 siswa. Hasil analisa perkembangan kepribadian siswa pada siklus I diperoleh nilai 47,50 dengan kategori kurang baik. Hasil analisa perkembangan kepribadian siswa pada siklus II diperoleh nilai 74,17 dengan kategori cukup baik, dengan peningkatan sebesar 26,67 dan rata-rata skor penilaian 6,83. Selain itu kegiatan guru membina siswa dengan teknik Eklektif Attending pada siklus I tergolong cukup baik yaitu 61,67. Sedangkan kegiatan guru membina siswa dengan teknik Eklektif Attending pada siklus II memperoleh nilai 90 dengan kategori sangat baik. Berdasarkan data hasil wawancara siswa yang dibimbing menggunakan teknik Eklektif attending pada siklus I dan siklus II ternyata cukup aktif dalam mengikuti proses belajar mengajar. Dari hasil analisis data pada siklus I dan II tersebut dapat dilihat bahwa terjadi peningkatan kemampuan siswa menyelesaikan permasalahan yang dihadapi dan prestasi belajar siswa dalam kelas dengan menggunakan Teknik Eklektif Attending. Kata kunci: konseling, ekletif attending